Poor responses to oseltamivir treatment in a patient with influenza A (H7N9) virus infection - Xuhui Liu; Tao Li; Yufang Zheng; Ka-Wing Wong; Shuihua Lu; Hongzhou Lu (Emerging Microbes and Infections, 2013)
In March 2013, the cases of human infection with influenza A of H7N9 subtype were first reported. Preliminary data suggested that the H7N9 isolates are sensitive to neuraminidase inhibitors, such as oseltamivir, which is the recommended choice of treatment. On April 2nd, a 56-year-old male patient was presented with fever and cough to our hospital. He had previous history of close contact with another H7N9 patient. After caring for his wife (a confirmed H7N9 infection case died on April 3rd), this patient showed flu like symptoms on April 2nd. On the same day, oseltamivir (75 mg bid) treatment was started. Throat swab specimens were screened for H7N9 virus by real-time reverse transcriptase-polymerase chain reaction. The patient was hospitalized on April 4th. Initial specimens on April 4th and April 5th were negative for H7N9. But the specimen collected on April 10th was tested positive for H7N9. The result was confirmed by Shanghai Municipal Center of Disease Control and Prevention. By April 25th when we submitted this report, swab specimens of this patient were still positive for H7N9. This case calls for increased awareness of potential resistance of H7N9 to oseltamivir.